Subversive : Christ, culture, and the shocking Dorothy L. Sayers - Downing, Crystal (Broadleaf Books, 2020)
Known for her bestselling detective novels, Dorothy L. Sayers lived a fascinating, groundbreaking life as a novelist, feminist, Oxford scholar, and important influence on the spiritual life of C.S. Lewis. Subversive shows how Sayers ignites new ways to think about Christianity, shocking people into seeing the truth of ancient doctrine; inspiring believers to evaluate how and why their language perpetuates divisive certitude rather than the hopeful faith; and showing us all a better way forward.